Faulkner’s Sanctuary: Horace Benbow and the Phenomenology of Evil - Moore, Robert (FOCUS: Papers in English Literary and Cultural Studies, 2000)
William Faulkner’s Sanctuary has conventionally been read as his most pessimistic novel, one with a vision so bleak and despairing that it leaves the reader with no suggestion of reconciliation or redemption. If, however, the novel is read as Faulkner’s exploration of the nature of evil, Sanctuary becomes a more complex work, one deserving of the respect and attention usually reserved for The Sound and the Fury, Light in August, and Absalom, Absalom!